Reverse thinking: Taking a healthy diet perspective towards food systems - Brouwer, Inge D.; Liere, Marti J. van; de Brauw, Alan; Dominguez-Salas, Paula; Herforth, Anna; Kennedy, G.; Lachat, Carl; Omosa, Esther van; Talsma, Elise F.; Vandevijvere, Stephanie; Fanzo, Jessica; Ruel, Marie T. (International Fund for Agricultural Development, 2022)
Food systems are failing to deliver healthy, accessible diets while not exceeding the boundaries of planetary resources. The international community has called for food systems transformation and policy solutions to secure healthy diets for all. These strategies, however, focus on supply and the market rather than a healthy diet perspective. This paper argues that food systems transformation should incorporate a dietary perspective that is guided by information on diets, dietary trends, consumer motives, and the food environment characteristics. It shows that dietary trends differ by food system development stage, thus different transformational approaches are required. It reviews the knowledge on drivers of consumer choices and discusses conflicting objectives and trade-offs among the multiple food systems actors. It outlines promising policy options and reflects on how a dietary perspective may contribute to sustainable food systems transformations.